Antibacterial Activity against Gram-Positive and Gram-Negative Bacteria and Biolarvicide to Aedes aegypti from Cocok Bubu (Elatostema rostratum (Blume) Hassk) Leaves Extract - Lela Lailatul Khumaisah; Rika Ayuningtias; Salih Muharam; Reni Mulyani; Luthfi Awaliah (Universitas Andalas, 2023)
Tropical diseases are infectious diseases that commonly occur in tropical climates. Infectious diseases are caused by bacteria, viruses, parasites, and are transmitted by several vectors. There are 8 neglected tropical diseases (NTDs) that have spread in Indonesia. Therefore, massive efforts are needed to overcome this disease. Active plant substances have long been popular in treating various diseases. Cocok Bubu (Elatostema rostratum (Blume) Hassk) is an endemic plant of Indonesia. Ethnobotanical studies of this plant are used to treat fever and diarrhea. But, there are no pharmacological studies on previous research because this species belongs to a limited distribution plant. However, Elatostema has a secondary metabolite with various pharmacological activities. This study aims to determine the activity of antibacterial and biolarvicides from Cocok bubu leaf extract. The extraction using the maceration method with acetone, phytochemicals screening, toxicity test using BSLT, antibacterial test with disc diffusion to Escherichia coli, Staphylococcus aureus, Streptococcus mutant, and Streptococcus sanguinis, and biolarvicide activity against Aedes aegypti. Based on the results, Cocok bubu leaf extract contains flavonoids, alkaloids, saponin, tannin, terpenoids, and steroids with a toxicity of 758.45 ppm. From antibacterial activity results, Cocok bubu exctract had the best inhibition zone against Staphylococcus aureus (10 – 18 mm). According to the biolarvicide test, it is effective as a biolarvicide to Aedes aegypti with LC50 51.099 ppm and LT50 of 5 h 43 min. This study shows that Cocok bubu was more effective for treating and preventing NTDs in Indonesia, especially dengue and chikungunya fever in the future.